Pengembangan Aplikasi Bahan Ajar Pendidikan Agama Islam Berbasis Android di Sekolah Menengah Atas - Rohinah, Rohinah (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2015)
The rapid advancement of technology has penetrated in all aspects of human life. Man in her life now are making use of technology to facilitate their work, which creates a dependency so that technology becomes a primary thing. No doubt human daily activities is now inseparable from the role of technology. So also in the field of education that has memanfaatan technology to facilitate the learning activities in order to achieve better results. One of the technologies used in mobile learning education is already included in the ICT-based learning. This research aims to produce teaching materials on Islamic Education (PAI) android-based upper secondary schools. This research is a type of development research.. The data collection method used were interviews, observation and documentation. Data analysis used is descriptive analysis. The results of research that has been developed in the form of application application that is packaged in a * apk directly from MIT App Inventor software. The application is in getting through Bluetooth or download at google play store with the name "PAI Chapter IX".